Dr. Fur, new halal serum for cats - Fist, . (Faculty of Industrial Sciences & Technology (FIST), 2018)
1. Program Jalinan Inovasi UMP – SK Taman Rinting 2 2. Exchange Program: Industrial Biotechnology Program with Three Asian Nations 3. Basic LaTeX Workshop 2018 4. Official Visit to Gas Processing Kertih, Petronas Gas Berhad 5. NDA with Emas Impresif Sdn Bhd 6. Dr. Fur, new halal serum for cats